The Grenada papers; with a foreword by Sidney Hook - Seabury, Paul (Institute for Contemporary Studies San FranciscoUS, 1984)
Presents a body of documents chronicling the internal affairs of Grenada, captured by U.S. military forces during the American invasion in October 1983.